Language Ideologies and Educational Inequality: Linguistic Hierarchies in an Elite Multilingual School in Jakarta - Asmi, Nur; Vania, Naomi; Asdi, Wansari (Jurnal Tahuri, 2022)
This study investigates how language ideologies shape and reproduce educational inequality in an elite multilingual school in Jakarta. In Indonesia’s multilingual context, where Bahasa Indonesia functions as the national language alongside hundreds of local languages, English has assumed a dominant role in elite private schools adopting international curricula such as Cambridge. Within this setting, English serves as the primary medium of instruction, Bahasa Indonesia is used mainly for informal communication, and local languages are virtually absent. The research explores how linguistic hierarchies are constructed, practiced, and legitimized through classroom discourse and institutional policy, and how these hierarchies affect students’ learning experiences and access to educational opportunities. Using a qualitative design, data were collected through classroom observations, semi-structured interviews with teachers, students, and administrators, and document analysis of language policies, syllabi, and promotional materials. Data were analyzed using Critical Discourse Analysis (CDA) within the frameworks of Language Ideology Theory and Bourdieu’s linguistic capital. Findings reveal that English functions as high-status linguistic capital associated with intelligence, global citizenship, and socioeconomic privilege, while Bahasa Indonesia occupies a pragmatic and subordinate role. Students from non-English-speaking backgrounds face subtle linguistic and social barriers, reinforcing educational stratification. The study contributes to Southeast Asian sociolinguistics by highlighting how elite multilingual education sustains symbolic inequality and calls for more inclusive language policies balancing global and national identities.